Rethinking the School of Salamanca - Reviewed: The School of Salamanca: A Case of Global Knowledge Production. Edited by Thomas Duve, José Luis Egío, and Christiane Birr. Leiden: Brill, 2021. Pp. 430. $ 32.00 (digital). ISBN: 9781108498265 - Domingo, Rafael (Journal of law and religion, 2022)
The history and influence of the School of Salamanca is attracting the attention of researchers from very different branches of knowledge and from a very wide variety of countries around the world. Broaching this subject invites one to reflect on both the unity of knowledge and the important role that theology plays in a secularized world. In this short essay, I discuss four recently published works that show the global scope of interest in Spanish Scholasticism in general and the School of Salamanca in particular. The first, The School of Salamanca: A Case of Global Knowledge, was edited by Thomas Duve, Jose Luis Egío, and Christiane Birr in coordination of the Max Planck Institute (2021). The second work, ¿Qué es la Escuela de Salamanca?, was edited by Simona Langella and Rafael Ramis-Barceló (2021). The third work is a recent thematic compendium on Spanish Scholasticism edited by Harald E. Braun, Erik De Bom, and Paolo Astorri (2022). Finally, I discuss David Lantigua’s monograph, Infidels and Empires in a New World Order: Early Modern Spanish Contributions to International Legal Thought (2020).